2016
DOI: 10.3346/jkms.2016.31.12.2002
|View full text |Cite
|
Sign up to set email alerts
|

Do Somatic Symptoms Predict the Severity of Depression? A Validation Study of the Korean Version of the Depression and Somatic Symptoms Scale

Abstract: This study aimed at exploring the psychometric characteristics of the Korean Version of the Depression and Somatic Symptoms Scale (DSSS) in a clinical sample, and investigating the impact of somatic symptoms on the severity of depression. Participants were 203 consecutive outpatients with current major depressive disorders (MDD) or lifetime diagnosis of MDD. The DSSS was compared with the Montgomery-Åsberg Depression Rating Scale (MADRS) and the 17-items Hamilton Depression Rating Scale (HAMD). The DSSS showed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
8
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 21 publications
0
8
0
1
Order By: Relevance
“…The data for a probable diagnosis of depression were based on the second measure at 2 weeks, during which the correlation between SGDS-K and K-HDRS was the highest (r=0.753; P =.01). To develop a diagnostic model, participants were classified into 2 groups: depression (SGDS-K≥7 and K-HDRS≥8) and nondepression (SGDS-K≤6 and K-HDRS≤7) groups [39-41]. Finally, 18 older adults were classified into the depression group and 29 were classified into the nondepression group (Figure 2).…”
Section: Methodsmentioning
confidence: 99%
“…The data for a probable diagnosis of depression were based on the second measure at 2 weeks, during which the correlation between SGDS-K and K-HDRS was the highest (r=0.753; P =.01). To develop a diagnostic model, participants were classified into 2 groups: depression (SGDS-K≥7 and K-HDRS≥8) and nondepression (SGDS-K≤6 and K-HDRS≤7) groups [39-41]. Finally, 18 older adults were classified into the depression group and 29 were classified into the nondepression group (Figure 2).…”
Section: Methodsmentioning
confidence: 99%
“…These physical symptoms are strongly correlated with the onset and outcome of depression and anxiety (Preis, Golm, Kröner‐Herwig, & Barke, ). Clinical observations have shown that the severity of gastrointestinal symptoms and neurotrophic symptoms in patients with depression is significantly associated with suicidal tendency in patients with depression, with mild physical symptoms increasing the suicidal intention of depressed patients by 1.136 times and severe physical symptoms increasing the risk by 2.028 times (Jeon et al, ; Jeong et al, ). The hypothalamus controls the release of endocrine hormones through the pituitary gland and connects nerves through the autonomic nervous system and other pathways to regulate sleep, body temperature and feeding (Caron & Richard, ; Markakis, ).…”
Section: Introductionmentioning
confidence: 99%
“…The reliability and validity of the Chinese, Korean, and English versions of the DSSS have been established (Hung et al, 2006a;Jeon et al, 2016;Tse et al, 2018). Several validities of the DSSS among patients with depression have been tested, as follows.…”
mentioning
confidence: 99%
“…Several validities of the DSSS among patients with depression have been tested, as follows. (1) The DS score is significantly correlated with the scores of the Hamilton Depression Rating Scale (HAMD), Montgomery-Asberg Depression Rating Scale, Center for Epidemiologic Studies Depression Scale, and mental subscales of the Short-Form 36 (Hung et al, 2006a;Jeon et al, 2016;Tse et al, 2018). ( 2) The DS is sensitive to pharmacotherapy-the improvement percentage of the DS score after four weeks of pharmacotherapy is correlated with that of the HAMD score (Hung et al, 2006a).…”
mentioning
confidence: 99%
See 1 more Smart Citation